Collagen type VI interaction improves human islet survival in immunoisolating microcapsules for treatment of diabetes. Issue 2 (4th March 2018) - Llacua, L. Alberto; Hoek, Arjan; de Haan, Bart J.; de Vos, Paul
ABSTRACT: Collagens are the most abundant fibrous protein in the human body and constitute the main structural element of the extracellular matrix. It provides mechanical and physiological support for cells. In the pancreas, collagen VI content is more than double that of collagen I or IV. It is a major component of the islet-exocrine interface and could be involved in islet-cell survival. To test the impact of collagen VI on human encapsulated pancreatic islets-cells, we tested the effects of exogenous collagen type VI on in vitro functional survival of alginate encapsulated human islet-cells. Concentrations tested ranged from 0.1 to 50 µg/ml. Islets in capsules without collagen type VI served as control. Islet-cell interaction with collagen type VI at concentrations of 0.1 and 10 µg/ml, promoted islet-cell viability (p<0.05). Although no improvement in glucose induced insulin secretion (GSIS) was observed, islets in capsules without incorporation of collagen type VI showed more dysfunction and oxygen consumption rates was improved by inclusion of collagen type VI. Our results demonstrate that incorporation of collagen type VI in immunoisolated human islets supports in vitro viability and survival of human pancreatic islets.